2022
DOI: 10.3390/s22166112
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Estimation of Oscillator Parameters: Toward Anomaly Detection and Cyber-Physical System Security

Abstract: Cyber-physical system security presents unique challenges to conventional measurement science and technology. Anomaly detection in software-assisted physical systems, such as those employed in additive manufacturing or in DNA synthesis, is often hampered by the limited available parameter space of the underlying mechanism that is transducing the anomaly. As a result, the formulation of anomaly detection for such systems often leads to inverse or ill-posed problems, requiring statistical treatments. Here, we pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Data-driven machine learning techniques are under investigation and implementation as a possible first line of defense against cyberattacks given their propensity to model complex relationships (not easily described through explicit rules) to automatically discover (new) cyberattack patterns and anomalous modes of operation. Machine learning for the security of general cyber-physical systems (Lukens et al, 2022) as well the more specific security of the smart grid is an active area of research (Ashrafuzzaman et al, 2020;Karimipour et al, 2019;Khaw et al, 2020;Jahromi et al, 2020, Jahromi et al, 2021Zhang et al 2021) that has already shown promising results. The authors in Ashrafuzzaman et al (2020) develop an ensemble technique that can classify different kinds of cyberattacks; the technique works well, but there is potential for improvement in the case of very heavily imbalanced data.…”
mentioning
confidence: 99%
“…Data-driven machine learning techniques are under investigation and implementation as a possible first line of defense against cyberattacks given their propensity to model complex relationships (not easily described through explicit rules) to automatically discover (new) cyberattack patterns and anomalous modes of operation. Machine learning for the security of general cyber-physical systems (Lukens et al, 2022) as well the more specific security of the smart grid is an active area of research (Ashrafuzzaman et al, 2020;Karimipour et al, 2019;Khaw et al, 2020;Jahromi et al, 2020, Jahromi et al, 2021Zhang et al 2021) that has already shown promising results. The authors in Ashrafuzzaman et al (2020) develop an ensemble technique that can classify different kinds of cyberattacks; the technique works well, but there is potential for improvement in the case of very heavily imbalanced data.…”
mentioning
confidence: 99%